Covid-19 & Prophylaxis of Ischemic Stroke - Ali, Md Amir; Islam, Aminul; Chowdhury, RU; Hasan, Md Shafiqul; Rahman, Abu Hasnat Md Habibur; Mukherjee, Sudipta Kumer; Ashrafee, Pariza (Bangladesh Journal of Neurosurgery, 2021)
Background: Corona viral disease-19 (COVID-19) is the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The whole world is panic about this culprit small virus. It accelerates procoagulation that produce ischemic stroke. Our endeavor is to prevent ischemic stroke. Anti-coagulant and or thrombin inhibitor may be helpful to be prophylactic therapy of ischemic stroke in COVID-19 patients specially with D-dimer positive, severe complications & co-morbidities. Methods: Total of 76 patients were diagnosed as SARS-CoV-2 and they had been first time reported & were admitted in Combined Military Hospital (CMH) Mymensingh, within 1st March 2020 to 15th August 2020. Total of 76 cases in either sex & age variables were randomly selected and divided into two groups one with severe form of disease, procoagulation co-morbidities, coagulopathy-mainly D-dimer positive and another simple COVID-19. Out of 76 patients simple COVID-19 were 41(53.95%) and complex 35(46.05%). Diagnosis was based upon history, clinical examination, and X- ray/Computed Tomography (CT) scan of chest and confirmatory by Reverse transcription polymerase chain reaction (RT-PCR). Results: Total 76 patients COVID-19 were admitted in CMH Mymensingh within 1st March 2020-15th August 2020 and were evaluated by details history, clinical examination & relevant investigation. Here males were 68 (89.47%); females were 8(10.53%) & males were predominant. COVID-19 incidence among the age group; young adult and adult were higher, 10-19 years 06(7.89%), 20-29 years 26(34.21%) and 30-39 years 24(31.58%), 40-49 years 15(19.74%) and 50 years or more 5(6.58%) in number. Out of 76 patients, 35(46.05%) patients were given anticoagulant and thrombin inhibitor therapy. Of that 35 patients 14(40%) patients were D-dimer positive, 8(22.86%) patients were cardiovascular disorder (HTN with hypercholesteromia, MI), 5(14.29%) were DM, severe pulmonary oedema 3(8.57%) and multiple co-morbidities 5(14.29%) in number but not given to simple COVID-19 patients. There were 4 patients who died amongst 76 patients; one with HTN,MI, 2nd one with heart failure , 3rd one with HTN, Old haemorrhagic stroke and last one with CKD and severe pulmonary oedema and mainly they are above 50 years of age and fortunately no one died with ischemic stroke. Follow- up all patients 02 weeks after SARS-CoV-2 negative and there were no patients suffered from ischemic stroke. Conclusion: Prevention is always better than cure. Since COVID-19 produce prothrombotic state followed by ischemic stroke, so better to use prophylaxis of ischemic stroke those who are prone; by induce anti-coagulant and or thrombin inhibitor. Bang. J Neurosurgery 2021; 10(2): 163-168